Vibration simulation of a simply-supported beam with attached multiple absorbers - Idris, Mohd Azli (2015)
In general, the standard solutions to reduce the vibration and noise problems are to redesign and modify the system such as adding the thickness of wall panels, enhancing the elasticity of the structure and increase the damping mechanism of the structure. In this study, the concept of dynamic vibration absorber is used on a beam structure to re-duce the vibration or amplitude. The methods employed in this study were analytical equations and finite element analysis. MATLAB® was used to transform analytical equations into graphs and at the same time to verify the finite element simulation of ANSYS®. Result shows that analytical equation and finite element simulation of a simply supported beam produce a similar outcome, which indicates a good agreement. The frequency range was studied between 5 Hz to 1000 Hz and there are four modes resulting shape. Further study was conducted by placing the absorber at different lo-cations configuration. This was followed by adding a single absorber and multiple absorbers to see the average percentage reduction in vibration’s amplitude. The over-all reduction achieved for multiple absorbers is 88.6% compared to a single absorber which only achieved 8.21% reduction. Finally, it can be concluded that multiple vi-bration absorber can be reduce the global vibration of structure compared to a single vibration absorber. However, for the structures that concern about weight, adding more dynamic vibration absorber needs to be considered properly since excess weight will result in less fuel efficiency of vehicles, aerospace, automotive and machine systems.